Hubungan supervisi kepala ruangan dengan kinerja perawat pelaksana - Nawangwulan, Rahayu; Fitriani, Dewi; Yuannita, Riri; Utami, Sesilia (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2023)
Background: Nurses really determine the quality of health services in the hospital. Efforts to meet service standards by nurses while on duty are one of the indicators for the performance of nurses in carrying out their duties, in this case supervision needs to be done so that they can help or ensure that what the nurse is doing is correct and in accordance with the procedure. Purpose: Of this study was to determine the relationship between the supervision of the head of the room and the performance of the nurses in the Inpatient Installation of Dr. Sitanala Tangerang. Method: Is a descriptive analytic study with a correlational study using a questionnaire and observation sheets to measure the supervision of the head of the room with the performance of the nurse executives, this study uses a cross sectional research method. The number of samples was 82 respondent nurses who worked in the Inpatient Installation of Dr. Central General Hospital. Sitanala Tangerang with total sampling technique. Result: The results obtained from 82 respondents obtained results almost entirely with good supervision of the head of the room as much as 92.7% and mostly with good performance of the nurse as much as 80.5%. The results of statistical tests obtained a value (p-value = 0.001, α: 0.05), Conclusion: it can be concluded that there is a relationship between the supervision of the head of the room and the performance of the nurse in charge. Keywords: Supervision of Head of Room; Performance of Implementing Nurses. Pendahuluan: Tenaga perawat sangat menentukan kualitas pelayanan kesehatan di rumah sakit. Upaya pemenuhan standar pelayanan oleh perawat saat bertugas menjadi salah satu indikator kinerja perawat dalam melaksanakan tugasnya, dalam hal ini supervisi perlu dilakukan agar dapat membantu atau memastikan apa yang dilakukan oleh perawat pelaksana sudah benar dan sesuai dengan prosedur. Tujuan: Untuk mengetahui hubungan supervisi kepala ruangan dengan kinerja perawat pelaksana di Instalasi Rawat Inap Rumah Sakit Umum Pusat Dr. Sitanala Tangerang. Metode: Penelitian deskriptif analitik dengan studi korelasional yang menggunakan kuesioner dan lembar observasi untuk mengukur supervisi kepala ruangan dengan kinerja perawat pelaksana, penelitian ini memakai metode penelitian cross sectional. Jumlah sampel sebanyak 82 responden perawat pelaksana yang bekerja di Instalasi Rawat Inap Rumah Sakit Umum Pusat Dr. Sitanala Tangerang dengan tehnik total sampling. Hasil: Penelitian diperoleh dari 82 responden didapatkan hasil hampir seluruhnya dengan supervisi kepala ruangan baik sebanyak 92.7% dan sebagian besar dengan kinerja perawat pelaksana baik sebanyak 80.5%. Hasil uji statistik diperoleh nilai (p-value=0.001, α:0.05) Simpulan: ada hubungan supervisi kepala ruangan dengan kinerja perawat pelaksana. Kata Kunci: Supervisi Kepala Ruangan; Kinerja Perawat Pelaksana.